Peer Social Support Relations with Student Academic Stress - Mila Afifah Yulius; Firman Firman (Universitas Negeri Padang, 2020)
Self-determination is the ability of individuals to choose and determine the actions to be achieved in determining their future. Self-determination includes three indicators namely competence, autonomy and interrelation. If the individual or adolescent has low self-determination, he will perform actions or behaviors in accordance with peer group members, in this case related to peer conformity. conformity is behavior that arises because of the desire of individuals to imitate the attitudes and behavior of others, peers make it difficult for adolescents to believe in themselves and tend to trust more in peer groups. This study aims to: (1) describe the level of peer conformity in adolescents, (2) describe the level of teen self-determination, (3) test whether there is a significant relationship between peer conformity and adolescent self-determination.This type of research uses a quantitative approach with a correlational description method, with a sample of 249 students from SMA Negeri 12 Padang, using Stratified random sampling technique. The instrument used in this study was a questionnaire distributed via the Google forms application. Based on likert scale. Data were analyzed with descriptive statistical techniques and Pearson Product Moment correlation techniques with the help of the SPSS program.The results revealed that: (1) Peer conformity was in the moderate category with a frequency of 48%, (2) self-determination was in the moderate category with a frequency of 33%, and (3) There was a significant positive relationship between peer conformity with self-determination with coefficient correlation of 0.282 with a significance level of 0,000.